Spontaneous renal artery dissection masquerading as urinary tract infection. (21st October 2018) - Chamarthi, Gajapathiraju; Koratala, Abhilash; Ruchi, Rupam
Abstract : Spontaneous renal artery dissection is a rare clinical entity, and symptoms vary from non-specific abdominal pain to life-threatening hypertension. A 44-year-old woman with no significant medical history initially presented with symptoms suggestive of urinary tract infection which did not respond to antibiotic therapy. Imaging revealed right renal infarction resulting from focal spontaneous renal artery dissection, which was managed conservatively. CT angiography is the preferred imaging modality for the diagnosis of this condition. Treatment options include medical management of hypertension with or without anticoagulation, endovascular intervention and surgical revascularisation depending on the presentation and the extent of the vascular and renal parenchymal involvement. This case emphasises the need to have high index of suspicion for uncommon diagnoses in patients who present with common symptoms but do not respond to empiric therapy.